Composición florística, estructura y estado de conservación del bosque siempre verde montano bajo de la cordillera del Condor -Kutuku, en la microcuenca El Padmi, Zamora Chinchipe - Ecuador - Cuenca Jiménez, Leonor Leticia (2015)
This research was conducted in the neighborhood "The Padmi" parish Los Encuentros, canton province of Zamora Chinchipe Yantzaza to determine the floristic composition, structure and condition of the Condor-Kutukú micro evergreen forest Montano Bajo de la Cordillera " The Padmi "ran from August 2014 to December 2015 month For removal of information a permanent plot of 10,000 m2, divided into 25 subplots of 400 m2 (20 x 20 m) for more trees or settled DAP equal to 5 cm within the subplots at random five plots of 25 m2 (5 x 5 m) for shrubs and five plots of 1 m2 (1 x 1 m) for herbs were installed. Density (D), relative density (DR), relative dominance (DMR), relative frequency (RF) and importance value index (IVI) The following environmental parameters are calculated. To determine the structure of forest basal area and volume per diameter class was calculated. structural sections was performed using a transect of 10 x 100 m, where trees are recorded in distances X and Y. The condition of the forest was analyzed based on a quantitative and qualitative analysis consists of 6 variables, 25 indicators and 100 technical criteria. In the permanent plot 164 species on the plot, spread over 126 tree species, 20 shrubs, 6 and 12 epiphytic herbs recorded. 1519 individuals / ha greater than or equal to 5 cm of DAP, with a basal area of 50.46 m2 / ha and a total volume of 673.77 m3 / ha were recorded. The most diverse families were Rubiaceae, Meliaceae, Moraceae, Euphorbiaceae, Annonaceae and Lauraceae. The most ecologically important species were: Nectandra reticulata, Virola glycycarpa, Otoba parvifolia, Vochysia paraensis, Elaeagia obovata, Grias peruviana, Inga acreana and Wettinia maynensis in the tree layer, the most abundant species in the shrub layer was: Piper sp. and Asplundia schizotepala in the herbaceous layer. According to the assessment of the conservation status Lower Montane evergreen forest of the watershed is good.